Hell or high water : surviving Tibet's Tsangpo River - Heller, Peter, 1959- (Rodale : Distributed to the trade by Holtzbrinck Publishers, 2004)
It is the Everest of rivers, a maelstrom of water and rocks, gradient and flow. It is the world's last great adventure prize, remote, forbidding, and hidden from Western eyes. Long considered unrunnable, the Tsangpo River has drawn extreme kayakers since the sport was born. It's killed them too. One group did it. A mammoth, old-school adventure team led by a young, fiery river cowboy battled the white water, their Sherpa, and a Himalayan winter to log the first descent of the Tsangpo. Peter Heller, himself an accomplished kayaker, was along for the ride. In this beautifully written and exciting tale, he takes us into the water and down the cataclysmic vertical drops, painting a portrait of a grand adventure in a place that time never touched.